„The Cult of Asianism“:: Asiendiskurse in Indien zwischen Nationalismus und Internationalismus (ca. 1885–1955) - Fischer-Tiné, Harald (Comparativ, 2008)
The article explores Asianist discourses that emerged in India from the late9th century through the first decade after independence. The first section gives a general overview of the various historical stages of the Indian involvement with Asia during the period under survey as expressed in the writings and speeches of leading intellectuals and politicians. The second section analyses in greater detail three of the most important discursive constructions of a pan-Asian identity from the interwar period: Rabindranath Tagore’s influential anti-modernist conception of ‘Asia as spiritual counter-Europe’; the powerful trope of Asia as ‘Greater India’, that gained particular popularity among Hindu nationalist outfits; and the pragmatic and modernist concept of Young Asia’, that posited a pan-Asian solidarity as a strategic device in the fight against Western imperialism. With the possible exception of the ‘Young Asia’ model, it is argued by way of conclusion, the Indian ‘cult of Asianism’ was clearly built on Western Orientalist stereotypes and had only limited potential to contribute to the intellectual decolonisation of India.